Current knowledge on the microbiota of edible insects intended for human consumption: A state-of-the-art review. (November 2019) - Garofalo, Cristiana; Milanović, Vesna; Cardinali, Federica; Aquilanti, Lucia; Clementi, Francesca; Osimani, Andrea
Abstract: Because of their positive nutritional characteristics and low environmental impact, edible insects might be considered a 'food of the future'. However, there are safety concerns associated with the consumption of insects, such as contaminating chemical and biological agents. The possible presence of pathogenic and toxigenic microorganisms is one of the main biological hazards associated with edible insects. This review presents an overview of the microbiota of edible insects, highlighting the potential risks for human health. Detailed information on the microbiota of edible insects from literature published in 2000–2019 is presented. These data show complex ecosystems, with marked variations in microbial load and diversity, among edible insects as well as stable and species-specific microbiota for some of the most popular edible insect species, such as mealworm larvae ( Tenebrio molitor ) and grasshoppers ( Locusta migratoria ). Raw edible insects generally contain high numbers of mesophilic aerobes, bacterial endospores or spore-forming bacteria, Enterobacteriaceae, lactic acid bacteria, psychrotrophic aerobes, and fungi, and potentially harmful species (i.e. pathogenic, mycotoxigenic, and spoilage microbes) may be present. Several studies have focused on reducing the microbial contamination of edible insects by applying treatments such as starvation, rinsing, thermal treatments, chilling, drying, fermentation, and marination, both alone and, sometimes, in combination. Although these studies show that various heat treatments were the most efficient methods for reducing microbial numbers, they also highlight the need for species-specific mitigation strategies. The feasibility of using edible insects as ingredients in the food industry in the development of innovative insect-based products has been explored; although, in some cases, the presence of spore-forming bacteria and other food-borne pathogens is a concern. Recent studies have shown that a risk assessment of edible insects should also include an evaluation of the incidence of antibiotic-resistance (AR) genes and antibiotic-resistant microorganisms in the production chain. Finally, as proposed in the literature, microbial hazards should be limited through the implementation of good hygienic practices during rearing, handling, processing, and storage, as well as the implementation of an appropriate HACCP system for edible insect supply chains. Another issue frequently reported in the literature is the need for a legislative framework for edible insect production, commercialisation, and trading, as well as the need for microbiological criteria specifically tailored for edible insects. Microbiological criteria like those already been established for the food safety and hygiene (e.g. those in the European Union food law) of different food categories (e.g. ready-to-eat products) could be applied to edible insect-based products. Graphical abstract: Unlabelled Image Highlights: Edible insects harbour a complex microbial ecosystem. A stable and species-specific microbiota was revealed for some insect species. Edible insects may be reservoirs of AR genes and antibiotic-resistant microorganisms. The safety of insect-based products should be carefully evaluated.